From beeps to streets: unveiling sensory input and relevance across auditory contexts - Korte, Silvia; Jaeger, Manuela; Rosenkranz, Marc; Bleichner, Martin G. (Frontiers in Neuroergonomics, 2025)
IntroductionThis study investigates the neural basis of sound perception in everyday life using EEG data recorded in an office-like environment over 3.5 h. We aimed to understand how contextual factors such as personal relevance, task complexity, and stimulus properties influence auditory processing in ecologically valid settings.MethodsBy systematically increasing the complexity of acoustic scenes and tasks, we analyzed changes in neural responses, focusing on the N100 and P300 components.ResultsOur results show that while the P300 is a stable marker of attention in both isolated sounds and complex soundscapes, the N100 is more sensitive to task complexity and environmental factors.DiscussionThese findings highlight the importance of context in shaping auditory perception and suggest that laboratory-based findings can be partially generalized to real-world settings. At the same time, task demands significantly influence neural markers. This opens new opportunities to study sound perception in naturalistic environments without sacrificing the control typically afforded by laboratory studies.